O “espírito” da/e a modernidade religiosa à brasileira : um estudo socioantropológico das relações, perspectivas e recomposições dos pentecostalismos na moderna sociedade no Brasil - Barrozo, Victor Breno Farias (2020)
The present thesis aims to study religious modernity to Brazilian, from the socio-anthropology of religions, analyzing the relationships, perspectives and recompositions of Pentecostalisms in modern society in Brazil. As a central issue, we place ourselves in a comprehensive interpretation of the meanings and social functions of religion in modern times, through a particular examination of Pentecostals and the modern world in the country. In a context of national modernization throughout the 20th century, while several religious groups - such as Roman Catholicism and historical Protestantism - experienced a process of crisis and weakening, Pentecostals in Brazil have become one of the main religious expressions of the country and. According to data from the 2011 Pew Reserch Center, Pentecostals and Charismatics across the globe accounted for some 584.080 billion followers - corresponding to 8.5% of the world's population and 26.7% of the percentage of Christians in the world - distributed across a myriad denominations, movements and communities. The Brazilian Institute of Geography and Statistics (IBGE), according to data from the 2010 Census, pointed out that Brazil has about 25,370,483 million Pentecostals, making up 12.9% of the country's population. In this research, using a theoretical-methodological approach, we seek to carry out a genealogical and historical reconstruction of this theme, returning to the classics (such as Durkheim and Weber), passing through contemporary authors (and their perspectives), as well as a comparative look at religion and modernity in different global contexts, in order to highlight the central elements of that binomial and the evidence of “multiple religious modernities”. Then, we focus on dealing with the explanation of national researchers on religion and modernity in Brazilian society, underlining their specificities, processes and dynamics. Finally, the place and connections between Pentecostalism and the modern world will be presented, evoking academic analyzes of interfaces (such as issues of globalization, secularization and individualism) and the “movements” - decomposition, composition and recomposition - of the Pentecostal field modern Brazilian. Our hypothesis is that Pentecostalisms are, at the same time, a product and producer of a religious modernity in Brazil, being able to lend themselves to the elucidation of this phenomenon. Considering these points, this work seeks to discuss the characteristics and specificities of a typical Brazilian religious modernity, through the observation of the case of Pentecostals in modern society in the country.